Pelatihan Protokol CHSE Bagi Karyawan Restoran Kantin Chinese Food - Wulanmeiaya Wowor; Yuki S. Hensen; Shania Silke; Wilhelmina Rosse Marisca Gajeng (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2022)
The COVID-19 pandemic that has hit the world has had a profound impact on the operations of the food and beverage industry. In order to survive, various efforts were made. One of them is by implementing the CHSE (Cleanliness, Health, Safety, and Environmental Sustainability) protocol. The Chinese Food Canteen Restaurant is a restaurant that wants to carry out this endeavor. It aims to survive and rebuild the trust of its customers. However, its employees do not yet have knowledge of the CHSE protocol. For this reason, it is necessary to conduct CHSE protocol training to equip its employees. The CHSE training held is a collaboration with the UPH Faculty of Tourism. In addition to increasing knowledge, this training also aims to improve employee skills so that customer trust can increase again. The training method used is explanation and direct practice. The results of the training achieved are that the employees of the Chinese Food Canteen Restaurant have knowledge of the CHSE protocol and can apply it in restaurant operations.